Pomembnost interkulturnih svetovalnih kompetenc po mnenju učiteljev v osnovni šoli - Javornik Krečič, Marija (Revija za elementarno izobraževanje, 2010)
The society of today is a mosaic of different cultures, made up of a mixture of their characteristics. Because of this, the subject of this article is teachers' opinions about intercultural counseling. In the first part of the article a theoretlcal basis of the inter-cultural element in the classroom is presented. The role of intercultural counseling is also dealt with, which is an important (supportive) factor for teachers who are facing a stressful intercultural environment. The results of the empirical research, which was made in June 2009, are introduced in the second part of the article. The aim of the research, carried out among primary school teachers, was to discover their opinions about the competence of intercultural counseling.
Keywords: interkulturnost; interkulturno svetovanje; svetovalne kompetence; romski otroci; šolska svetovalna služba